2014
DOI: 10.1016/j.jbiomech.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of assessing trunk motor control using position and force tracking and stabilization tasks

Abstract: System-based methods have been applied to assess trunk motor control in people with and without back pain, although the reliability of these methods has yet to be established. Therefore, the goal of this study was to quantify within- and between-day reliability of assessing trunk motor control using systems-based methods involving position and force tracking and stabilization tasks. Ten healthy subjects performed six tasks, involving tracking and stabilizing of trunk angular position in the sagittal plane, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…Our findings are consistent with a previous study conducted by our group(Reeves et al, 2014) that used similar tasks and input signal characteristics for assessing trunk motor control. We observed similar trends to the Reeves et al (2014) study in which tracking tasks were shown to be more reproducible than a position stabilization task.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with a previous study conducted by our group(Reeves et al, 2014) that used similar tasks and input signal characteristics for assessing trunk motor control. We observed similar trends to the Reeves et al (2014) study in which tracking tasks were shown to be more reproducible than a position stabilization task.…”
Section: Discussionsupporting
confidence: 93%
“…The methods used in this study were based on a previous publication by our group investigating trunk motor control(Reeves et al, 2014). We have adapted the same methods to investigate head-neck motor control and the description of these methods was taken from the published material with some slight modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative reliability was quantified using intraclass correlation coefficients (ICCs), while the standard error of measurement (SEM) was calculated to quantify absolute reliability (Atkinson and Nevill, 1998), which indicates the precision of the measure (Weir, 2005). These measures have been employed to assess the reliability of various kinetic, kinematic, neuromuscular, and performance measures in biomechanical research (Dankaerts et al, 2004;Hidalgo et al, 2012;Montgomery et al, 2011;Ng et al, 2003;Pitcher et al, 2008;Reeves et al, 2014;Stevens et al, 2006). ICCs range from 0.00 to 1.00, with higher values indicating greater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were explained by motor learning, changes in posture or stretching of the joints (Reeves et al, 2014;Lariviere et al, 2015;Popovich et al, 2015). In contrast, in a previous study no learning effects were found.…”
Section: Systematic Errorsmentioning
confidence: 99%